ANALISIS PERBANDINGAN PERHITUNGAN PAJAK PENGHASILAN FINAL PASAL 4 AYAT 2 SEBELUM DAN SESUDAH PENERAPAN PMK NOMOR 44/PMK.03/2020 TERHADAP PAJAK TERUTANG - Novita dwi cahyani (VALUE, 2022)
Changes to income tax incentives were made by the government to support the economy ofmicro and small entrepreneurs in reporting income taxes. The government providesincentives to micro and small business actors through the application of (PMK) Number44/PMK.03/2020 which was set on 27 April 2020. CV Cahaya Anugerah Technology is oneof the companies in Kediri that is engaged in providing services and selling electronicequipment. Before the Covid-19 pandemic, this company was able to pay taxes regularly.After the Covid-19 pandemic, many companies went bankrupt due to declining revenues.This study uses a descriptive type of research with a qualitative approach with the aim ofanalyzing, explaining, and concluding the impact of the application of (PMK) Number44/PMK.03/2020 on taxes payable. Data collection techniques in this study are in the formof documentation and interviews from CV Cahaya Anugerah Technology. The results of thisstudy indicate that the calculation of income tax in 2019 and 2020 can be seen that in2020 there are incentives. The incentive aimsto provide relief to companies in accordancewith PMK No. 44/PMK.03/2020.